Nurses' role in antibiotic stewardship at medical wards of a referral hospital in Malawi: Understanding reality and identifying barriers. (2021) - Mula, Chimwemwe Tusekile; Middleton, Lyn; Muula, Adamson; Solomon, Vernon; Varga, Christine
Abstract: Background: Nurses have multiple roles in medication management. In relation to antibiotics, nurses are recommended to be active in antibiotic stewardship that ensures proper management of antibiotics to minimize antibiotic resistance. Some of the roles of nurses include administering antibiotics, monitoring its effectiveness and educating the patient. Throughout the inpatient hospital stay, nurses communicate about patient antibiotic management with doctors, the pharmacy for medication supply and the laboratory for microbiology results. However, nurses' role is not explicitly included in international antimicrobial stewardship guidelines, suggesting that nurses' ability to promote antibiotic stewardship is not well established in policy. Additionally, there is little empirical research describing nurses' roles and challenges, especially in Malawi. The aim of this study was to explore nurses' roles and challenges in antibiotic stewardship. Methods: A case study design with a multiple data source triangulation strategy was used. Nurses' roles in antibiotic stewardship were explored using focus group discussions, participant observations and semi-structured interviews. Study participants were medical ward nurses, doctors, pharmacists and laboratory technologists in a large Malawian teaching and referral hospital. The data was analyzed using thematic analysis. Results: The main theme that emerged from nurses roles was that nurses have multiple antibiotic stewardship roles. The subthemes were: Nurses have a facilitating role in microbiology specimen investigations, Nurses have a role in contributing to prescription decisions and nurses have a role to ensure antibiotics are available at point of care. Two main themes identified from the challenges were competency gaps, multidisciplinary team work challenges and limited resources. Conclusion: The findings illustrate the need to recognize and support the nurses in their multiple antibiotic stewardship roles in low resource settings. Training, multidisciplinary team work and provision of resources would benefit nurses.